Effectiveness of Edmodo-Based Mobile Learning System Application In Physics Learning For XI MIPA Students SMA Negeri 1 Makassar - Fauziah, Andi; Junaedi, Subaer; Amin, Bunga Dara (Asian Journal of Science Education, 2023)
The research aims to determine the effectiveness of guided inquiry with Edmodo-based mobile learning system implementation in physics learning. Edmodo is a learning management system application developed for mobile learning that enables students to access tasks and teaching materials anytime and anywhere. This research was quasi-experimental that used a pretest-posttest control group design with 11th-grade students in SMAN 1 Makassar as a sample, and each class consisted of 33 students who were used as the experimental class and the control class. The sample selection was carried out using a purposive sampling technique. The instrument used in this study was a physics learning achievement test in the form of multiple-choice tests. Data were analyzed using the T-test on two samples with test equipment that had gone through expert validation tests and empirical tests. The result of the T-test analysis showed no difference in learning outcomes between experimental and control classes before being treated, this result contradicts the results of the T-test analysis after treatment which shows significant differences in physics learning outcomes in students taught using guided inquiry by applying a learning-based mobile learning system with students taught using guided inquiry without mobile learning system. Based on these two T-test results and by using Cohen-D analysis with the result of 2,980. Therefore, the application of a mobile learning system based on Edmodo is effective in improving physics learning students outcomes in class XI MIPA SMA Negeri 1 Makassar.